Kedudukan dan Perlindungan Hukum Justice Collaborator dalam Pengungkapan Jaringan Suap - Ratna Tresnawati; Rahmat Bakri; Kamal; Suardi Dg. Mallawa; Syachdin (Jurnal Ilmu Hukum, 2026)
Bribery as a form of organized corruption poses serious evidentiary challenges given its covert nature and the involvement of influential actors within circles of power. This study analyzes the legal standing of justice collaborators in bribery disclosure and evaluates the application of justice principles in their legal protection in Indonesia. It employs a normative juridical method with statutory, conceptual, and case-based approaches, analyzing legal materials qualitatively through deductive reasoning and comparison across judicial decisions. The findings reveal that although collaborator status is normatively recognized, its application remains inconsistent due to the absence of standardized eligibility criteria. Across six bribery cases, no collaborator received a sentence lighter than the prosecution's demand. Tommy Sumardi, Abdul Khoir, and Maliki were sentenced more heavily than demanded, the latter two after panels annulled the status granted by the Corruption Eradication Commission, while Andi Narogong's sentence rose from eight years at first instance to thirteen at cassation. This study recommends standardizing eligibility criteria through binding regulation, strengthening the binding force of witness protection agency recommendations, and codifying the collaborator's position within criminal procedural law.